Intelligent decision support system for road network planning - Deng Jun; Mo Yikui (2009 ISECS International Colloquium on Computing, Communication, Control, and Management, 2009)
Along with the rapid development of urban road transportation network and the incessantly upgraded level of system complexity, traditional methods in transportation planning are subject to more and more evident limitations. In the context when computer technology is experiencing fast growth, this article sets forth the idea that the standard of urban road network planning can be enhanced by applying an intelligent decision support system. With the use of artificial intelligence technology and network technology, this article is intended to build up a framework in the decision support system for urban road network planning, and to make a tentative examination on the building and design of decision support system in aspects of system structure, function modules and integrated modes. In addition, the appraisal index system and ways of decision analysis are also discussed in light of the features of road network planning, and such system is of significant importance in boosting the intelligence and efficiency level of road network planning.